Antibacterial mechanism of Kratom (Mitragyna speciosa) methanol extract on Streptococcus pneumoniae and Eschericia coli bacteria - Hotimah Masdan Salim; Marinda Dwi Puspitarini; Yuani Setiwati; Michio Shimabukuro (Biomolecular and Health Science Journal, 2021)
Introduction: Kratom (Mitragyna speciosa) is a tropical herbal plant native to the North Malay Peninsula, Malaysia and Thailand. In Indonesia, kratom us a typical plant of West Kalimantan, especially in Putussibau. Kratom leaf has many pharmacological effects, one of them is antioxidant. However, the antioxidant and antimicrobial activities of Mitragyna speciosa leaf extracts are lacking. This study was to examine the effect of the methanol extract of Mitragyna speciosa (Rubiaceae Family) leaves on microorganisms Escherichia coli and Strepococcus pneumoniae.Methods: Kratom leaves were extracted with methanol as solvent. In this study, S. pneumoniae and E. coli bacteria have been used. Antibacterial activity tests were carried out at concentrations of 0.78%, 1.56%, 3.125%, 6.25%, 12.5%, 25%, 50% and 100%. Insilico was used to search for secondary metabolites and metabolite interactions in Mytragina speciosa. Results: Mitragyna speciosa leaf methanol extract was effective in inhibiting the growth of E. coli and S. pneumoniae significantly (P<0.001). The growth of e.coli was not identified from a concentration of 25% to 100%. However, there was no bacterial growth in S. pneumoniae from a concentration of 6.25% to 100%. In the insilico study it was found that the secondary metabolite of Mitragyna speciosa is quercetin, which interacts with the ATP1 protein as a predictor in the mechanism of Mitragyna speciosa as an antibacterial. Conclusion: In conclusion, there is no correlation between nutritional status and remission outcome of patients with ALL in the induction phase of therapy. However, high percentage of underweight patients shows nutrition needs special attention to improve therapy outcomes.